2016
DOI: 10.1155/2016/6362812
|View full text |Cite
|
Sign up to set email alerts
|

Isosteviol Sensitizes sarcKATP Channels towards Pinacidil and Potentiates Mitochondrial Uncoupling of Diazoxide in Guinea Pig Ventricular Myocytes

Abstract: KATP channel is an important mediator or factor in physiological and pathological metabolic pathway. Activation of KATP channel has been identified to be a critical step in the cardioprotective mechanism against IR injury. On the other hand, desensitization of the channel to its opener or the metabolic ligand ATP in pathological conditions, like cardiac hypertrophy, would decrease the adaption of myocardium to metabolic stress and is a disadvantage for drug therapy. Isosteviol, obtained by acid hydrolysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, the involvement of alternative pathways is suggested in isosteviol-mediated myocardial protection. Recently, Fan and colleagues observed that when isosteviol was administered alone, it failed to produce any effects, whereas it increased the pinacidil-induced activation of sarcKATP channels and potentiated the diazoxide-mediated oxidation of flavoproteins in mitochondria, suggesting the engagement of mitoKATP channels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the involvement of alternative pathways is suggested in isosteviol-mediated myocardial protection. Recently, Fan and colleagues observed that when isosteviol was administered alone, it failed to produce any effects, whereas it increased the pinacidil-induced activation of sarcKATP channels and potentiated the diazoxide-mediated oxidation of flavoproteins in mitochondria, suggesting the engagement of mitoKATP channels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study investigated the effect of STV on sarc-and mitoK ATP channels and showed that STV could sensitize these K ATP channels in a ROS dependent manner [25]. We speculate that the ROS-mediated regulation of K ATP channel could also be a potential mechanism by which STV exert the anti-cardiac hypertrophic effect.…”
Section: Multiple Consensus Phosphorylation Sites For Pka and Pkc Havmentioning
confidence: 88%
“…Isosteviol is proposed to be able to reduce the infraction area and restore the contractility in cardiac IR in vivo and in isolated hearts without introducing or even improving arrhythmia. Our previous study on its effect on sarc-and mitoK ATP channels also indicated a potential cardioprotective effect of STV [25].…”
Section: Introductionmentioning
confidence: 86%
“…Epoxyeicosatrienoic acids, metabolites of arachidonic acid, are involved in the activation of PI3Kα and opening of K ATP channels, which prevent Ca 2+ overload and maintain mitochondrial function . Isosteviol sodium may increase the activation rate of sarcK ATP channels induced by pinacidil and potentiate the diazoxide‐elicited oxidation of flavoproteins in mitochondria …”
Section: Drug Therapy and Perspectivementioning
confidence: 99%
“…38 Isosteviol sodium may increase the activation rate of sarcK ATP channels induced by pinacidil and potentiate the diazoxide-elicited oxidation of flavoproteins in mitochondria. 39 The new antihypertensive drug iptakalim activates K ATP channels in the endothelial cells of resistance blood vessels, a mechanism that is dependent on ATP hydrolysis and specific ATP ligands. The functions of endothelial K ATP channels in resistance blood vessels can be changed by the exposure to the high shear stress caused by hypertension.…”
Section: Drug Therapy and Perspectivementioning
confidence: 99%